2014
DOI: 10.3174/ajnr.a4152
|View full text |Cite
|
Sign up to set email alerts
|

MS Lesions Are Better Detected with 3D T1 Gradient-Echo Than with 2D T1 Spin-Echo Gadolinium-Enhanced Imaging at 3T

Abstract: BACKGROUND AND PURPOSE:In multiple sclerosis, gadolinium enhancement is used to classify lesions as active. Regarding the need for a standardized and accurate method for detection of multiple sclerosis activity, we compared 2D-spin-echo with 3D-gradient-echo T1WI for the detection of gadolinium-enhancing MS lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…Furthermore, we used three-dimensional gradient-echo T1-weighted sequences to detect contrast enhancement. Although some studies have suggested that three-dimensional spin-echo sequences are more sensitive for contrast enhancement than gradient-echo sequences (25), others have come to the opposite conclusion (26,27). However, we improved sensitivity for contrast enhancement by calculating intensity-harmonized subtraction maps between preand postcontrast T1-weighted images.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we used three-dimensional gradient-echo T1-weighted sequences to detect contrast enhancement. Although some studies have suggested that three-dimensional spin-echo sequences are more sensitive for contrast enhancement than gradient-echo sequences (25), others have come to the opposite conclusion (26,27). However, we improved sensitivity for contrast enhancement by calculating intensity-harmonized subtraction maps between preand postcontrast T1-weighted images.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that use of 3D gradient-echo or 3D fast spin-echo sequences at 3.0 T yields higher detection rates for gadolinium-enhancing MS lesions (especially smaller ones) than do standard 2D gradient-echo sequences, with better suppression of artefacts related to vascular pulsation. 95,96 Diffusion-weighted imaging Other MRI sequences have been proposed as potential add-ons in the diagnostic work-up of patients with MS. Diffusion-weighted imaging (DWI) can enable differentiation of an acute MS lesion from an acute ischaemic lesion: gadolinium-enhancing MS lesions show increased diffusivity, whereas ischaemic lesions show decreased diffusivity. 97 However, during a short and very early phase of lesion evolution (first few hours or days), transient diffusion restriction (high signal intensity on DWI and reduced apparent diffusion coefficient) has been described in some acute MS lesions.…”
Section: Follow-up Examinationsmentioning
confidence: 99%
“…A recent study conducted by Crombé et al 34 showed higher detection rates at 3.0 T for Gd-enhancing lesions (especially smaller ones) using a 3D-MPRAGE sequence than using standard 2D gradient-echo sequences, with better suppression of artifacts related to vascular pulsation 34 and the additional advantage of the ability of the generated dataset to be subsequently reformatted to obtain high-quality images in any plane. However, we found that this finding was not confirmed on 1.5 T scanners, as observed by other authors [35][36][37] .…”
Section: A B C Discussionmentioning
confidence: 98%